Mitochondrial DNA markers reveal high genetic diversity and strong genetic differentiation in populations of Dendrolimus kikuchii Matsumura (Lepidoptera: Lasiocampidae). - Qiulei Men; Guoxi Xue; Dan Mu; Qingling Hu; Minyi Huang (PLoS ONE)
Dendrolimus kikuchii Matsumura, 1927 is a serious forest pest causing great damage to coniferous trees in China. Despite its economic importance, the population genetics of this pest are poorly known. We used three mitochondrial genes (COI, COII and Cytb) to investigate the genetic diversity and genetic differentiation of 15 populations collected from the main distribution regions of D. kikuchii in China. Populations show high haplotype and nucleotide diversity. Haplotype network and phylogenetic analysis divides the populations into three major clades, the central and southeastern China (CC+SEC) clade, the eastern China (EC) clade, and the southwestern China (SWC) clade. Populations collected from adjacent localities share the same clade, which is consistent with the strong relationship of isolation by distance (r = 0.74824, P = 0.00001). AMOVA analysis indicated that the major portion of this molecular genetic variation is found among the three groups of CC+SEC, EC and SWC (61.26%). Of 105 pairwise FST comparisons, 93 show high genetic differentiation. Populations of Puer (PE), Yangshuo (YS) and Leishan (LS) are separated from other populations by a larger genetic distance. Distributions of pairwise differences obtained with single and combined gene data from the overall populations are multimodal, suggesting these populations had no prior population expansion in southern China. The nonsignificant neutral test on the basis of Tajima' D and Fu's Fs, and the lack of a star-shaped haplotype network together with the multiple haplotypes support this hypothesis. Pleistocene climatic fluctuations, combined with the host specificity to Pinus species, made these regions of south China into a refuge for D. kikuchii. The high level of population genetic structuring is related to their weak flight capacity, their variations of life history and the geographic distance among populations.